A composite additive for forming core-shell structure inclusions, preparation and smelting method
The core-shell structural inclusions prepared by using Fe-Zr-Ti-Mg-RE composite additives solves the problem that inclusions in steel affect the performance of steel, and achieves the performance improvement of steel materials.
Patent Information
- Application Number
- CN202310971995.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-08-03
AI Technical Summary
The prior art is difficult to effectively control and improve the formation process and microscopic mechanism of inclusions in steel, resulting in poor performance of steel resistance to fatigue and local corrosion resistance.
Using a composite additive with chemical compositions of Fe: 41-59%, Zr: 5-11%, Ti: 14-26%, Mg: 11-19%, RE: 4-10%, prepared by smelting and casting of vacuum induction furnaces, used to smel steel materials to form fine, spheroidized and dispersed core-shell structural inclusions.
It significantly improves the plasticity, toughness, fatigue resistance, local corrosion resistance, welding performance and cold bending performance of steel materials, and is suitable for a variety of high-performance steel types.
Smart Images

Figure CN117230276B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of smelting, and in particular to a composite additive for forming core-shell structure inclusions, and a preparation and smelting method. Background Art
[0002] Steel materials are the foundation of the manufacturing industry and the most important structural material used in human society. They play a vital role in economic and social development. Steel purification technology is the basis for producing high-performance and high-quality products. Since the 1980s, the cleanliness of steel has been continuously improved. However, these materials still have service properties such as fatigue resistance and local corrosion resistance that cannot meet the requirements of economic and social development during use. The main reason is the lack of in-depth understanding of the formation process, microscopic mechanism and control method of inclusions in steel. Inclusions in steel (mainly oxide inclusions) seriously affect the quality of steel. The presence of inclusions in steel destroys the continuity of the metal and reduces the mechanical properties, physical properties, chemical properties and process properties of steel. Inclusions in steel mainly exist in the form of non-metallic compounds, such as oxides, sulfides, nitrides, etc., which cause uneven organization of steel and affect the physical, mechanical and chemical properties of steel. Inclusions in steel reduce the plasticity, toughness and fatigue life of steel, deteriorate the processing performance of steel, and have a direct impact on the surface finish, welding performance and local corrosion resistance of steel. For example, inclusions in steel can cause surface defects in thin steel plates for automobiles and electrical products, cracks in thin steel plates for DI tanks, hydrogen-induced cracks in pipeline steel, breakage during tire meridian processing, and deterioration of fatigue properties of bearing steel. At the same time, non-metallic inclusions in steel also have adverse effects on the steel plate's tear resistance, low-temperature impact toughness, and seawater corrosion resistance.
[0003] The smelting, pouring and solidification of steel is a complex physical and chemical process. Intrinsic inclusions are various compounds generated by complex chemical reactions during the liquid and solidification process of steel. When the molten steel solidifies, they do not have time to float up and are embedded in the steel; or they are non-metallic substances dissolved in steel at high temperatures. When the temperature of the molten steel decreases, the solubility of these non-metallic substances in the steel decreases and they precipitate from the steel and exist in the steel in the form of inclusions.
[0004] Among them, oxide inclusions in steel are the main types of inclusions. Oxides such as Al2O3, MgO, CaO, and composite oxides such as calcium aluminate, magnesium aluminate, and aluminum magnesium spinel are the main forms of oxides in steel. This type of inclusion is easily deposited inside the submerged nozzle, causing nozzle blockage, and can also cause surface defects in steel products, reducing the surface finish of the steel. Al2O3 is the most common oxide inclusion that has the greatest impact on steel quality. It is a brittle non-deformable inclusion with a large difference in thermal deformation capacity from the matrix. Under the stress of hot working, large pieces of Al2O3 and other brittle inclusions are deformed and broken into inclusions with sharp corners and distributed in chains in the matrix. These hard and irregular Al2O3 inclusions can scratch the matrix and generate a stress concentration field around the inclusions until voids or cracks are formed at the interface. For example, in medium and high carbon steels, especially in bearing steels and heavy rail steels, Al2O3 inclusions can become fatigue sources under the action of cyclic stress, and eventually the expansion of fatigue cracks will cause large pieces of metal to fall off, leading to the fracture of the steel.
[0005] For general structural steels, sulfides in steel have little effect on the strength of steel at room temperature, but their content and form have a great effect on the toughness of steel (such as section reduction and impact toughness, etc.), especially low-temperature toughness. For most steels, an increase in sulfur content will reduce the performance of steel. At hot working temperatures, MnS inclusions are easily stretched into long strips, resulting in anisotropy of steel toughness. The composition of sulfide inclusions also has a significant effect on product performance. Manganese sulfide inclusions are easily deformed during rolling, while calcium sulfide is harder and actually does not deform during rolling. Sulfides have the possibility of producing hydrogen-induced cracks. Because hydrogen is easily trapped by the elongated MnS inclusions, it reduces its resistance to hydrogen-induced cracks. The weldability, machinability, and mechanical properties of steel are also affected by the type and quantity of sulfide inclusions in steel. Sulfides that exist in a network in steel can cause hot brittleness of steel.
[0006] The influence of inclusions in steel on performance involves many factors. The number, particle size, shape and distribution of inclusions in steel, the bonding strength between inclusions and steel matrix, the size of plasticity and elastic coefficient of inclusions, as well as thermal expansion coefficient, hardness and many other factors will affect the performance of steel. If technical measures are taken to effectively control inclusions in steel, not only can their harmful effects be eliminated, but also their beneficial effects can be brought into play. Large and concentrated inclusions are very harmful to the performance of steel, while inclusions with dispersed distribution and fine particles can not only eliminate their harm, but sometimes also improve the performance of steel. For example: the use of fine, dispersed oxides with excellent high-temperature stability in steel can improve the welding performance of steel, especially the welding performance under conditions of high heat input resistance.
[0007] In general, ferromanganese, ferrosilicon and aluminum are often used as deoxidizers in the smelting process. The oxides formed by them combining with oxygen cannot float to the slag for removal, and become non-metallic inclusions in the steel. Nitrogen is also a harmful element in steel. Its solubility in steel is extremely low. At the same time, it has a great affinity with elements such as titanium, vanadium and niobium. In addition, molten steel can absorb a large amount of nitrogen from the atmosphere, so nitride inclusions are easy to appear in steel.
[0008] The existing Al deoxidation process, i.e., deoxidation with Al blocks, Al particles, Al wires, and Fe-Al alloys, is a conventional deoxidation technology. The deoxidation product Al2O3 is the most influential type of common oxide inclusions on steel quality. It is a brittle non-deformable inclusion with a large difference in thermal deformation capacity from the matrix. Under the stress of hot working, large pieces of Al2O3 and other brittle inclusions are deformed and broken into inclusions with sharp corners and distributed in the matrix in chains. These hard and irregularly shaped Al2O3 inclusions can scratch the matrix and generate a stress concentration field around the inclusions until voids or cracks are formed at the interface.
[0009] The existing Ca treatment is the most widely used smelting technology for improving the morphology of inclusions in contemporary metallurgy. Ca is a very good purifier for molten steel. It can not only deeply deoxidize, but also deeply desulfurize. After the molten steel is deoxidized, when [O] is already very low, the direct deoxidation reaction of Ca becomes a secondary process. At this time, it mainly reacts chemically with A1203 in the steel to form calcium aluminate. In this way, not only the deoxidation problem is solved, but also the A1203 inclusions in the steel are reduced. However, some calcium aluminate inclusions that have not been floated and removed still remain in the steel. For steel materials with special performance requirements such as local corrosion resistance, fatigue resistance, and severe cold resistance, the problem cannot be fundamentally solved.
[0010] The way to control non-metallic inclusions in steel is to reduce the generation of inclusions and the contamination of molten steel by foreign inclusions during the smelting and casting process, and to try to remove the inclusions already in the molten steel or reduce the harm of inclusions to the steel. The main process methods are: (1) Control of inclusions in converter smelting, including ① reducing supplementary blowing and minimizing the amount of slag to reduce the oxygen content at the end of the converter; ② increasing the MgO content and basicity of the converter final slag to reduce slag; ③ taking measures such as slag blocking, slag removal and slag modification during steel tapping; ④ slag washing and desulfurization during converter tapping to reduce the sulfur content of molten steel and inhibit the harm of sulfide inclusions. (2) Inclusion control during refining, including ladle argon blowing, tundish air curtain retaining wall, pressurization and decompression method (NK-PERM), ladle electromagnetic stirring, tundish centrifugal separation, crystallizer electromagnetic braking, calcium treatment process, etc.
[0011] The following elements can spheroidize oxides, sulfides or oxysulfides: calcium, tellurium, magnesium, rare earth, etc. The solid solubility of the above four elements in the matrix iron is very low. The reason why these elements can spheroidize sulfides is that the sulfides of these elements have low wettability to the steel matrix, high interface energy, and large contact angle, so they are spherical.
[0012] However, the above methods have their own disadvantages: (1) For calcium-treated steel: the method of adding calcium is relatively complicated: one is to add calcium to the molten steel by spraying in the ladle through a spray gun; the other is to add calcium by feeding with a cored steel wire. (2) For tellurium and selenium treated steel: ① Both elements are very expensive and are unpopular from an economic point of view; ② Both are toxic; ③ Tellurium will also cause hot brittleness during rolling. (3) For magnesium-treated steel: Since magnesium is very light, it is difficult to add it to the molten steel alone, and the yield is low. (4) For rare earth-treated steel: ① Rare earths are prone to generate radioactive dust during production and application, and the radioactive hazards generated cannot be ignored. ② The nozzle of rare earth-treated steel is prone to nodule formation during casting, and the nozzle nodule formation problem often occurs when deoxidizing with a strong deoxidizer such as A1. ③ Rare earth inclusions have a high specific gravity, generally between 5.5-6.5, and are not easy to float. Especially when excessive rare earth addition is used, harmful inclusions in the steel will increase, especially large-sized inclusions, and even produce brittle rare earth and iron intermetallic compounds that deteriorate the performance of the steel.
[0013] From the above analysis, it can be seen that whether it is the control of inclusions in converter smelting or the control of inclusions in the refining process, the process is complicated, involves many steps, and the equipment investment cost is high and the control is difficult. In view of this, the present invention provides a composite additive for forming core-shell structure inclusions, and a preparation and smelting method. Summary of the invention
[0014] The technical problem to be solved by the present invention is to provide a composite additive, preparation and smelting method for forming core-shell structure inclusions. The purpose is to provide a low-cost, simple process, inclusions forming core-shell structure, with small, spheroidized and dispersed effects, and significantly improve the plasticity, toughness, fatigue resistance, local corrosion resistance, welding performance, cold bending performance, etc. of steel materials.
[0015] In order to solve the above technical problems, the first aspect of the present invention is to provide a composite additive for forming a core-shell structure inclusion, which includes the following chemical components in terms of mass percentage: Fe: 41-59%, Zr: 5-11%, Ti: 14-26%, Mg: 11-19%, RE: 4-10%; the mass percentages of Zr element, Ti element, Mg element and RE element satisfy the formula: (Ti+Mg+RE) / Zr=4-8.
[0016] The roles of the above ingredients in the composite additive are as follows:
[0017] Zirconium: Zirconium is a commonly used deoxidizer, and because it is often combined with titanium or aluminum titanium for composite deoxidation, it forms fine and dispersed composite inclusions; this composite inclusion pins the grain boundary movement during the welding thermal cycle to limit the growth of austenite grains, and induces the nucleation of acicular ferrite during the austenite transformation process, so that the grains are effectively refined and the toughness of the coarse grain zone of the weld is improved; at the same time, zirconium is a strong carbide-forming element, and its role in steel is similar to that of niobium, vanadium, and titanium, forming carbides or nitrides, which can effectively refine the grains and are beneficial to the low-temperature performance of steel; but excessive zirconium will also lead to coarse particles and lose the function of inhibiting grain coarsening; therefore, the mass content of Zr in the present invention is 5-11wt%;
[0018] Titanium: Titanium has a strong affinity with oxygen, nitrogen and carbon, and is a good deoxidizer and an effective element for fixing nitrogen and carbon. Titanium oxide is considered to be the most effective nucleation inclusion in steel, which can effectively promote the nucleation of acicular ferrite and is widely used in oxide metallurgy. Titanium can form fine and dispersed TiN particles in steel, which can only be slowly dissolved when heated to above 1400°C in steel. During the welding thermal cycle, TiN particles effectively hinder the coarsening of austenite grains, which is conducive to improving toughness. TiN particles can effectively promote the formation of acicular ferrite and effectively improve the welding performance of steel. However, excessive Ti is not conducive to improving the performance of steel, and is prone to forming coarse titanium carbonitrides, which become crack sources and lead to reduced toughness. Therefore, the mass content of Ti in the present invention is 14-26wt%;
[0019] Magnesium: Magnesium is a strong deoxidizing element and a composite oxysulfide forming element. Magnesium can reduce the number of inclusions in steel, reduce their size, make their distribution uniform, and improve their morphology. Trace amounts of magnesium can improve the size and distribution of carbides in stainless steel. The carbide particles are small and uniform. The formed MgO inclusions have the effect of pinning the austenite grain boundaries and have a good control effect on the grain size. Therefore, the mass content of Mg in the present invention is 11-19wt%;
[0020] Rare earth: In steel materials, it can be used as a deoxidizer, especially lanthanum (La) and cerium (Ce). When they are added to molten steel, the extremely active rare earth elements can form extremely stable oxides, sulfides, and oxysulfides with elements such as O and S in the steel; the addition of rare earth elements significantly improves the mechanical properties and corrosion resistance of steel materials, and rare earth steel has also become a research hotspot and is used to develop steel materials that meet specific needs; therefore, the mass content of RE in the present invention is 4-10wt%.
[0021] It should be noted that, in the above formula (Ti+Mg+RE) / Zr, Ti, Mg, RE and Zr respectively represent their respective mass percentages, and the numerical value substituted into the above formula is the numerical value before the percentage sign. For example, the mass percentage of Ti is 20%, the mass percentage of Mg is 15%, the mass percentage of RE is 7%, and the mass percentage of Zr is 8%, then substitute into the above formula (Ti+Mg+RE) / Zr=(20+15+7) / 8=5.2.
[0022] The beneficial effects of the present invention are:
[0023] (1) The composite additive provided by the present invention has the characteristics of low cost, simple process, core-shell structure formed by inclusions, fineness, spheroidization and obvious dispersion effect, and significantly improves the plasticity, toughness, fatigue resistance, local corrosion resistance, welding performance, cold bending performance, etc. of steel materials.
[0024] (2) The composite additive of the present invention is suitable for steels with strict requirements on the morphology of inclusions, such as marine engineering steel, pipeline container steel, low-temperature container steel, bridge steel, iron tower steel, rail steel, bearing steel, gear steel, shield machine tool steel, cord steel, spring steel, cold heading steel, automobile steel, electrical steel, etc. The obtained inclusions have a core-shell structure composite inclusion with small, spheroidized, dispersed, and bulk modulus similar to that of the iron matrix, which can significantly improve the corrosion resistance of neutral water medium, seawater corrosion resistance, fatigue resistance, improve plastic toughness, reduce local stress concentration, etc.
[0025] Based on the above technical solution, the present invention can also be improved as follows.
[0026] Further, it includes the following chemical components in terms of mass percentage: Fe: 46-57%, Zr: 6-11%, Ti: 15-16%, Mg: 12-19%, RE: 9-10%.
[0027] Further, it includes the following chemical components in terms of mass percentage: Fe: 50%, Zr: 8%, Ti: 20%, Mg: 15%, RE: 7%.
[0028] Furthermore, the RE includes La element and Ce element, and the mass ratio of the La element to the Ce element is (70-90):(10-30).
[0029] Furthermore, the Zr is sponge metal zirconium and / or metal zirconium; the Mg is any one of metal magnesium block, magnesium particles, magnesium-zirconium alloy block, magnesium-zirconium alloy particles, or a combination of at least two thereof.
[0030] The second aspect of the present invention is to provide a method for preparing a composite additive for forming core-shell structure inclusions, comprising the following steps: first adding Zr, Ti and RE to a Fe-Ti alloy, then smelting in a vacuum induction furnace, and finally casting under vacuum conditions to obtain the composite additive.
[0031] Furthermore, the time for vacuum induction furnace smelting in the preparation method is 4-8 hours.
[0032] The third aspect of the present invention is to provide a smelting method, comprising the following steps:
[0033] (1) Using a converter or an electric arc furnace, molten iron and / or scrap steel is subjected to steelmaking, and the temperature and composition are adjusted to obtain molten steel;
[0034] (2) allowing the molten steel to enter a ladle, firstly performing pre-deoxidation, and then performing final deoxidation using any of the composite additives described above to obtain final deoxidized molten steel;
[0035] (3) The molten steel after final deoxidation is refined and continuously casted in sequence.
[0036] Furthermore, in step (1), the temperature of the molten steel is 1551-1690° C., and the free oxygen content in the molten steel is 101-399 ppm; step (2) specifically comprises: allowing the molten steel to enter a ladle, and pre-deoxidizing the molten steel in the ladle using a Fe-Si alloy or a Fe-Si-Mn alloy under micro-sub-bubble stirring to adjust the free oxygen content in the molten steel to 11-99 ppm, and then performing final deoxidation using the composite additive under micro-sub-bubble stirring to obtain final deoxidized molten steel; in step (3), the final deoxidized molten steel is first subjected to LF refining, VD refining, or RH refining, and then continuous casting.
[0037] Furthermore, in step (2), the amount of the composite additive added to each ton of the molten steel is 0.51-4.9 kg, wherein the composite additive is added to the molten steel in the form of block alloy or cored wire, and the particle size of the composite additive is 3-19 mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The morphology of inclusions in the low alloy high strength steel obtained by non-aqueous solution electrolytic extraction in the present invention;
[0039] Figure 2 The element distribution of inclusions in the low-alloy high-strength steel obtained by non-aqueous solution electrolytic extraction of the present invention;
[0040] Figure 3 The SEM morphology and EDS analysis of the inclusions in the conventional Al-deoxidized low-alloy high-strength steel of the present invention after electrolytic extraction;
[0041] Figure 4 is the precipitation curve of the particles of sulfide, nitride, etc. in the solidification process of the present invention;
[0042] Figure 5 The density of states of different oxides of the present invention; wherein, (a) Ti2O3, (b) ZrO2, (c) Al2O3 density of states, the dotted line is the Fermi surface;
[0043] Figure 6 The KAM test results after rare earth La composite deoxidation of the present invention; wherein, (a) IQ graph, (b) KAM graph;
[0044] Figure 7 It is the Young's modulus of the Fe matrix, Al2O3 and AlLaO3 inclusions of the present invention; wherein, (a) Fe matrix, (b) Al2O3, and (c) AlLaO3. DETAILED DESCRIPTION
[0045] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0046] Example 1
[0047] The present embodiment relates to a composite additive for forming a core-shell structure inclusion, which includes the following chemical components by mass percentage: Fe is 50wt%, Zr is 8wt%, Ti is 20wt%, Mg is 15wt%, RE is 7wt%, and the rest are unavoidable impurities, and the mass percentage of Zr element, Ti element, Mg element and RE element satisfies the formula: (Mg+Ti+RE) / Zr=5.2. Wherein the RE includes La element and Ce element, and the mass ratio of the La element to the Ce element is 80:20.
[0048] The present embodiment relates to a method for preparing a composite additive for forming a core-shell structure inclusion, comprising the following steps: based on Fe-Ti alloy, Zr, Ti and RE are added, wherein RE comprises lanthanum La and cerium Ce, La is 80%, Ce is 20%, after smelting in a vacuum induction furnace for 6 hours, casting under vacuum conditions. The Zr used in the composite additive is sponge metal Zr or metal Zr. The RE used in the composite additive is a mixed rare earth, comprising lanthanum La and cerium Ce, La is 80%, Ce is 20%. The Mg used in the composite additive is a metal magnesium block, magnesium particles, or a Mg-Zr alloy block, alloy particles.
[0049] A smelting method involved in this embodiment includes the following steps:
[0050] (1) adjusting the temperature and composition of the molten steel after steelmaking by using a converter or an electric arc furnace, adjusting the tapping temperature to 1620° C., and the free oxygen content in the molten steel to 250 ppm;
[0051] (2) After the molten steel enters the ladle, it is stirred with micro-sub-bubbles for 6 minutes, and then pre-deoxidized with Fe-Si alloy or Fe-Si-Mn alloy in the ladle to adjust the free oxygen content in the molten steel to 55 ppm. After stirring with micro-sub-bubbles for 4 minutes, it is finally deoxidized with a composite additive; the composite additive is added to the molten steel in the form of block alloy or cored wire, and the particle size of the composite additive is 11 mm; the amount of the composite additive added is 2.7 kg per ton of molten steel; and the molten steel after final deoxidation is obtained;
[0052] (3) The final deoxidized molten steel is then subjected to LF refining, VD refining, or RH refining according to conventional processes; and finally the refined molten steel is continuously cast according to conventional processes.
[0053] Example 2
[0054] The present embodiment relates to a composite additive for forming a core-shell structure inclusion, which includes the following chemical components by mass percentage: Fe is 46wt%, Zr is 11wt%, Ti is 15wt%, Mg is 19wt%, RE is 10wt%, and the rest are unavoidable impurities, and the mass percentage of Zr element, Ti element, Mg element and RE element satisfies the formula: (Mg+Ti+RE) / Zr=4. The RE includes La element and Ce element, and the mass ratio of the La element to the Ce element is 90:10.
[0055] The present embodiment relates to a method for preparing a composite additive for forming a core-shell structure inclusion, comprising the following steps: based on Fe-Ti alloy, Zr, Ti and RE are added, wherein RE comprises lanthanum La and cerium Ce, La is 90%, Ce is 10%, after smelting in a vacuum induction furnace for 4 hours, casting under vacuum conditions. The Zr used in the composite additive is sponge metal Zr or metal Zr. The RE used in the composite additive is a mixed rare earth, comprising lanthanum La and cerium Ce, La is 90%, Ce is 10%. The Mg used in the composite additive is a metal magnesium block, magnesium particles, or a Mg-Zr alloy block, alloy particles.
[0056] A smelting method involved in this embodiment includes the following steps:
[0057] (1) adjusting the temperature and composition of the molten steel after steelmaking by using a converter or an electric arc furnace, adjusting the tapping temperature to 1560° C., and the free oxygen content in the molten steel to 150 ppm;
[0058] (2) After the molten steel enters the ladle, it is stirred with micro-sub-bubbles for 5 minutes, and then pre-deoxidized with Fe-Si alloy or Fe-Si-Mn alloy in the ladle to adjust the free oxygen content in the molten steel to 20 ppm. After stirring with micro-sub-bubbles for 3 minutes, it is finally deoxidized with a composite additive; the composite additive is added to the molten steel in the form of block alloy or cored wire, and the particle size of the composite additive is 3-19 mm; the amount of the composite additive added is 0.70 kg per ton of molten steel; and the molten steel after final deoxidation is obtained;
[0059] (3) The final deoxidized molten steel is then subjected to LF refining, VD refining, or RH refining according to conventional processes; and finally the refined molten steel is continuously cast according to conventional processes.
[0060] Example 3
[0061] This embodiment relates to a composite additive for forming a core-shell structure inclusion, which includes the following chemical components by mass percentage: Fe is 57wt%, Zr is 6wt%, Ti is 16wt%, Mg is 12wt%, RE is 9wt%, and the rest are unavoidable impurities, and the mass percentage of Zr element, Ti element, Mg element and RE element satisfies the formula: (Mg+Ti+RE) / Zr=6.2. Wherein the RE includes La element and Ce element, and the mass ratio of the La element to the Ce element is 70:30.
[0062] The present embodiment relates to a method for preparing a composite additive for forming a core-shell structure inclusion, comprising the following steps: based on Fe-Ti alloy, Zr, Ti and RE are added, wherein RE comprises lanthanum La and cerium Ce, La is 70%, Ce is 30%, after smelting in a vacuum induction furnace for 7 hours, casting under vacuum conditions. The Zr used in the composite additive is sponge metal Zr or metal Zr. The RE used in the composite additive is a mixed rare earth, comprising lanthanum La and cerium Ce, La is 70%, Ce is 30%. The Mg used in the composite additive is a metal magnesium block, magnesium particles, or a Mg-Zr alloy block, alloy particles.
[0063] A smelting method involved in this embodiment includes the following steps:
[0064] (1) adjusting the temperature and composition of the molten steel after steelmaking by using a converter or an electric arc furnace, adjusting the tapping temperature to 1670° C., and the free oxygen content in the molten steel to 350 ppm;
[0065] (2) After the molten steel enters the ladle, it is stirred with micro-sub-bubbles for 8 minutes, and then pre-deoxidized with Fe-Si alloy or Fe-Si-Mn alloy in the ladle to adjust the free oxygen content in the molten steel to 80 ppm. After stirring with micro-sub-bubbles for 5 minutes, it is finally deoxidized with a composite additive; the composite additive is added to the molten steel in the form of block alloy or cored wire, and the particle size of the composite additive is 16 mm; the amount of the composite additive added is 3.9 kg per ton of molten steel; and the molten steel after final deoxidation is obtained;
[0066] (3) The final deoxidized molten steel is then subjected to LF refining, VD refining, or RH refining according to conventional processes; and finally the refined molten steel is continuously cast according to conventional processes.
[0067] Experimental example
[0068] The following is an observation, analysis and test of the main inclusion characteristics of the low alloy high strength steel prepared in Example 1, and the results are as follows:
[0069] (1) Core-shell structural characteristics of inclusions
[0070] in, Figure 1 and 2 The morphology and element distribution of inclusions in low alloy high strength steel obtained after non-aqueous solution electrolytic extraction. Figure 1 and 2 It can be seen that the inclusions are spherical in shape. The type of inclusions extracted by non-aqueous solution electrolysis is complex oxysulfide: the core of the inclusions is Zr, Ti, Mg, RE complex oxide, and the surface of the spherical particles is sulfide (MnS) and carbide (TiN).
[0071] Scanning electron microscopy was used to compare the types and sizes of inclusions in low-alloy high-strength steels with different amounts of composite additives. In conventional Al-deoxidized steel, oxide inclusions are clustered (reference: Deng Z, Zhu M. Evolution Mechanism of Non-metallic Inclusions in Al-Killed Alloyed Steel during Secondary Refining Process [J]. Isij International, 2013, 53 (3): 450-458.), inclusions are mainly concentrated within 2-5 μm, and sulfides are strip-shaped, usually 5-20 μm in length; after composite deoxidation treatment, the size of inclusions is significantly refined, mainly concentrated within 1-3 μm (such as Figure 3 ).
[0072] (2) Composite deoxidation thermodynamics
[0073] In the above-mentioned test example (1), inclusions were observed and analyzed. The inclusions are a core-shell structure with sulfur oxides as the core and nitrides and sulfides attached to the periphery. This section conducts a thermodynamic analysis on the formation and evolution of composite inclusions. Considering the diversity of alloying elements in steel, a series of physical and chemical reactions will occur during the steelmaking process and the solidification process of molten steel to form non-metallic inclusions such as oxides, sulfides and nitrides. The Gibbs free energy change is a criterion for determining whether a reaction can proceed spontaneously at constant temperature and pressure. ΔG < 0 indicates that the reaction can occur spontaneously. The deoxidation reaction equation and thermodynamic formula involved in adding alloying elements to molten steel are shown in equations (1) and (2).
[0074]
[0075]
[0076] In the formula, ΔG and ΔG θ are the Gibbs free energy and standard Gibbs free energy of the reaction (J / mol), R is the gas constant (J / (mol·K)), T is the temperature (K), a i Indicates the activity of the element. Table 1 gives the corresponding Gibbs free energy data for the formation of possible inclusions in low alloy high strength steel, and the molten steel temperature is set to 1873K. As shown in Table 1, according to the value of Gibbs free energy, the formation order of pure metal oxides is Al2O3 (-734.33 kJ / mol), La2O3 (-610.85 kJ / mol), Ti2O3 (-273.72 kJ / mol), ZrO2 (-156.09 kJ / mol), and CaO (-96.36 kJ / mol). In addition, Zr and RE can completely or partially replace the Al element in Al2O3 in the molten steel to form ZrO2 (-7298.12 kJ / mol) and LaAlO3 (-646.15 kJ / mol). The Ca element can react with molten aluminum and oxygen to form calcium aluminate (-9458.40 kJ / mol). In the traditional aluminum deoxidation technology used in steelmaking, Al2O3 dominates the inclusions. At the same time, refractory bricks easily react with Al2O3 to form Al2O3·MgO (similar to spinel).
[0077] Table 1 Gibbs free energy of inclusion formation reaction at 1873K
[0078] serial number Chemical reactions <![CDATA[ΔG θ (J / mol)]]> ΔG(kJ / mol) 1 <![CDATA[2[Al]+3[O]=(Al2O3)]]> -1682927+323.240T -734.33 2 <![CDATA[[Mg]+2[Al]+4[O]=(MgO·Al2O3)]]> -1848696+574.144T <![CDATA[ΔG θ =-773.32]]> 3 <![CDATA[[Zr]+2[O]=(ZrO2)]]> -845532+266.100T -156.09 4 <![CDATA[2[Ti]+3[O]=(Ti2O3)]]> -1072872+346.000T -273.72 5 [Ca] + [O] = (CaO) -138227-63.000T -96.36 6 <![CDATA[[Ca]+6[Al]+4[O]=[CaO·Al2O3]]]> -1023637+142.120T -9458.40 7 <![CDATA[2[La]+3[O]=(La2O3)]]> -542531+124.150T -610.85 8 <![CDATA[3[Zr]+2(Al2O3)=4[Al]+3(ZrO2)]]> -8233279+464.510T -7298.12 9 <![CDATA[3[Zr]+2(Ti2O3)=4[Ti]+3(ZrO2)]]> -1073389+538.830T -11.99 10 <![CDATA[[La]+3[O]+[Al]=(LaAlO3)]]> -801616+129.000T -646.15 11 <![CDATA[[Ce]+(Al2O3)=(CeAlO3)+[Al]]]> -423900-247.300T -833.13 12 [Ca] + [S] = (CaS) -542531+124.150T -126.03 13 [Ti]+[N]=(TiN) -307620+113.400T 65.09
[0079] Composite deoxidation using Zr, Ti, Mg, and RE (rare earth) elements can easily form composite sulfur oxides in molten steel. Thermodynamic calculations were performed using Zr, La, and Ce alloying elements as examples (Formulas 3-6). The results show that Zr can directly react with Ti2O3 and Al2O3 (Formulas 3 and 4), and the composite addition of Zr and Ti deoxidizing elements will lead to a uniform distribution of composite oxides of Zr and Ti in molten steel. This provides theoretical support for the addition of Zr to modify common inclusions in steel (such as Al2O3). Formulas 5 and 6 show that under low oxygen concentrations, RE elements can directly react with Al in molten steel to form (La, Ce)-AlO3.
[0080]
[0081]
[0082]
[0083]
[0084] Among them, ΔG and ΔG θ , (J / mol) represent Gibbs free energy and standard Gibbs free energy respectively, R is a constant, (J / (mol·k)), T represents temperature, (K), a i represents the activity of element I, J1, J2, J3, and J4 represent In the low alloy high strength steel of the embodiment, the melting temperature is set to 1873K, and the corresponding Gibbs free energies are -7298.12 kJ / (mol·K), -11.99 kJ / (mol·K), -646.152 kJ / (mol·K), and -833.13 kJ / (mol·K), respectively. All Gibbs free energies are negative, indicating that all reactions can proceed spontaneously.
[0085] (3) Formation mechanism of complex sulfur oxides
[0086] Table 2 shows the solid solubility product formulas for carbides, nitrides, and sulfides. Figure 4 The figure shows the precipitation curve of the molten steel during the solidification and cooling process calculated using JMatPro thermodynamic software. Figure 4 It can be seen that nitrides begin to precipitate and grow at about 1400°C, and sulfides precipitate and grow at about 1300°C. Carbonitrides begin to precipitate at a low temperature of about 1100°C. In the later stage of the solidification process, CaS and TiN are mainly precipitated on the surface of the pre-formed oxide inclusions. Therefore, after composite deoxidation by Zr, Ti, Mg, and RE (rare earth) elements, the molten steel is continuously cast or molded, and then rolled to obtain Figure 1Composite inclusions with core-shell structure are seen.
[0087] Table 2 Solid solubility product formulas for carbides, nitrides and sulfides
[0088]
[0089]
[0090] MnS and ZrO2 have very similar lattice constants, see Table 3 for specific data. Since MnS and ZrO2 have a good lattice matching relationship, this will reduce the interface energy between the two. Lower interface energy will result in better adhesion between grains at different interfaces. This further proves why no strip-shaped or string-shaped sulfides were formed in the test samples. This is because MnS tends to precipitate on preformed ZrO2 particles, so the sulfides are refined, spheroidized and dispersed. This is beneficial to improve the plasticity and toughness of Zr and Mg composite deoxidized ferrite stainless steel.
[0091] Table 3 Lattice constants of MnS and ZrO2
[0092]
[0093] (4) Mechanism of fine dispersion of composite deoxidized inclusions
[0094] Density of states (DOS) is a useful tool for analyzing the electronic structure of solids. Figure 5 As shown. For Ti2O3, there is no gap at the Fermi surface, indicating that it has metallic properties. For ZrO2 and Al2O3, the gap energy at the Fermi surface is 3.5eV and 6.3eV respectively. The larger the gap energy, the stronger the insulating property of the material. At 1273K, the electrical conductivity of Ti2O3, ZrO2 and Al2O3 is 10 2 Ω- 1 m -1 , 10 -1 Ω -1 m -1 and 10 -2 Ω -1 m -1 The DOS data is consistent with the conductivity data in the literature (Zhang X, Qin R. Controlled motion of electrically neutral microparticles by pulsed direct current [J]. 2015, 5: 10162.).
[0095] The electrical conductivity of oxides is a key factor in their movement in molten steel. According to existing research results, the driving force for the movement of Al2O3 in molten steel is greater than that of ZrO2. During the refining and electrification process, ZrO2 particles tend to repel each other and are difficult to agglomerate, while Al2O3 easily collides with each other to form large particles, which float to the surface of molten steel and are absorbed by the surface covering agent of molten steel. Therefore, compared with conventional Al deoxidation, composite deoxidation with Zr, Ti, Mg, and RE can form fine, dispersed composite oxides, among which Figure 1 and 2 The experimental results prove this point.
[0096] According to the basic principles of metallurgical thermodynamics, Zr, Ti, Mg, and RE are all strong oxide-forming elements. Using Zr, Ti, Mg, and RE for composite deoxidation is beneficial to remove the free oxygen content in the molten steel. The density of the main oxides in steel is shown in Table 4. As can be seen from Table 4, the density of ZrO2 is 5.68 g / cm 3 , which is greater than the density of Al2O3 (3.97 g / cm 3 ), especially the density of ZrO2 and molten steel (7.15g / cm 3 ) is closer. Rare earth oxides have a higher density than ZrO2 (6.87 g / cm 3 ), so the addition of rare earth makes the density of composite oxides closer to the density of molten steel. Therefore, once stable oxides are formed at high temperature, composite oxides mainly composed of ZrO2 and rare earth oxides can float evenly in the molten steel, while Al2O3 will collide and gather on the surface of the molten steel to become a component of slag. The part of Al2O3 that fails to float will remain in the steel as large clusters of inclusions.
[0097] Table 4 Density of molten steel and various inclusions
[0098]
[0099] (5) Physical mechanism of the close relationship between the bulk modulus of inclusions and that of the iron matrix
[0100] Table 5 shows the crystal structures of the selected iron matrix and inclusions, and Table 6 shows the physical properties of the relevant inclusions determined by combining the first principle calculation. According to the calculation results, the bulk modulus of LaAlO3 (192.61) and La2O7Zr2 (165.83) are lower than those of Al2O3 (249.54) and ZrO2 (271.06), and the bulk modulus of LaAlO3 (192.61) is closer to the iron matrix (194.76). Other inclusions, such as CaO (114.11), MgO (165.84), TiN (175.02) and CaS (57.05), show lower bulk modulus than the matrix.
[0101] Table 5 Crystal structure parameters of inclusions and BCC matrix
[0102]
[0103]
[0104] Table 6 Calculation results of physical properties of inclusions and matrix
[0105]
[0106]
[0107] (6) Characterization of local stress of composite inclusions
[0108] Electron back-scattering diffraction (EBSD) technology can provide information on the crystal orientation, phase distribution and strain of the material microstructure. In this test work, the EBSD test selected a voltage of 20kV and a current of 13nA. In order to determine the lattice distortion between the inclusions and the matrix, it is necessary to eliminate the influence of external stress on the inclusions as much as possible. Therefore, the polished sample needs to be further polished using an argon ion polisher (GATAN 685). The image quality (IQ) map tested by EBSD is mainly used to describe the pattern quality of EBSD. Specifically, the strain distribution in the microstructure is represented by the change in pattern quality. For example, when the lattice is distorted, the IQ map will produce a diffuse, lower-quality diffraction pattern, and the grayscale in the IQ map will also increase accordingly. The local orientation difference distribution map (Kernel Average Misorientation, KAM) can be used to characterize the local stress concentration or the degree of homogenization of the lattice distortion. Generally, a higher KAM value indicates a higher degree of deformation / dislocation density in the area, and the larger the KAM value, the higher the stress concentration.
[0109] Figure 6 To develop the EBSD characterization results of the area containing composite inclusions in the steel sample. The results show that the IQ image quality in the sample is clear; the KAM map shows that the area around the composite inclusions is mainly blue (low strain), that is, there is only a relatively small strain concentration around the composite inclusions. It can be seen that the composite inclusions formed after rare earth La composite deoxidation produce very little stress in the matrix. The addition of rare earth elements is beneficial to the formation of rare earth composite inclusions in steel, such as LaAlO3 and La2O7Zr2, which is beneficial to reduce the stress caused by the presence of inclusions.
[0110] (7) Mechanism of the effect of rare earth addition on the physical properties of composite inclusions
[0111] The addition of rare earth elements affects not only the grain size and microstructure, but also the type and physical properties of inclusions. Rare earth (RE) elements have a stronger affinity for oxygen and sulfur than Zr, Ti and other deoxidizers, and can form rare earth oxides and rare earth sulfides, as well as rare earth composite inclusions composed of other deoxidizers, such as LaAlO3, La2O7Zr2, etc. Compared with Al2O3, the bulk modulus of LaAlO3 is closer to that of the Fe matrix, indicating that LaAlO3 inclusions have similar incompressibility to the matrix. In addition, the Young's modulus of LaAlO3 is also closer to that of the Fe matrix ( Figure 7 ), Young’s modulus is proportional to the hardness of the material, that is, the hardness of rare earth composite inclusions is closer to that of the matrix.
[0112] In summary, compared with the traditional Al deoxidation process, the rare earth composite inclusions formed by the rare earth deoxidation process can reduce the micro gaps between the inclusions and the matrix, so that uniform deformation occurs between the inclusions and the iron matrix, which is beneficial to improving the mechanical properties, fatigue resistance, and local corrosion resistance of the steel.
[0113] It can be seen from the above results that the composite additive and smelting method are particularly suitable for steels with strict requirements on the morphology of inclusions, such as marine engineering steel, pipeline container steel, low-temperature container steel, bridge steel, tower steel, rail steel, bearing steel, gear steel, cord steel, spring steel, cold heading steel, automotive steel, electrical steel, bridge steel, cable steel, stainless steel, H-shaped steel, etc. The obtained inclusions have a core-shell structure composite inclusion that is small, spheroidized, dispersed, and has a bulk modulus similar to that of the iron matrix, which can significantly improve the corrosion resistance to neutral aqueous media, seawater corrosion, fatigue resistance, improve plastic toughness, reduce local stress concentration, etc.
[0114] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0115] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A composite additive for forming a core-shell structure inclusion, characterized in that: It includes the following chemical components in terms of mass percentage: Fe: 41-59%, Zr: 5-11%, Ti: 14-26%, Mg: 11-19%, RE: 4-10%; the mass percentages of Zr, Ti, Mg and RE satisfy the formula: (Ti+Mg+RE) / Zr=4-8; The RE includes La element and Ce element, and the mass ratio of the La element to the Ce element is (70-90):(10-30).
2. A composite additive for forming core-shell structure inclusions according to claim 1, characterized in that: It includes the following chemical components in terms of mass percentage: Fe: 46-57%, Zr: 6-11%, Ti: 15-16%, Mg: 12-19%, RE: 9-10%.
3. A composite additive for forming core-shell structure inclusions according to claim 1, characterized in that: It includes the following chemical compositions in terms of mass percentage: Fe: 50%, Zr: 8%, Ti: 20%, Mg: 15%, RE: 7%.
4. A smelting method, characterized in that: The steps include: (1) Using a converter or an electric arc furnace, molten iron and / or scrap steel is subjected to steelmaking, and the temperature and composition are adjusted to obtain molten steel; (2) allowing the molten steel to enter a ladle, firstly subjecting it to pre-deoxidation, and then subjecting it to final deoxidation using the composite additive according to any one of claims 1 to 3, to obtain final deoxidized molten steel; (3) The molten steel after final deoxidation is successively refined and continuously cast.
5. A smelting method according to claim 4, characterized in that: The temperature of the molten steel in step (1) is 1551-1690° C., and the free oxygen content in the molten steel is 101-399 ppm. Step (2) specifically comprises: allowing the molten steel to enter a ladle, and firstly performing pre-deoxidation on the molten steel in the ladle using a Fe-Si alloy or a Fe-Si-Mn alloy under stirring with micro argon bubbles, adjusting the free oxygen content in the molten steel to 11-99 ppm, and then performing final deoxidation using the composite additive under stirring with micro argon bubbles to obtain final deoxidized molten steel. In step (3), the final deoxidized molten steel is firstly subjected to LF refining, VD refining or RH refining, and then subjected to continuous casting.
6. A smelting method according to claim 4, characterized in that: In step (2), the amount of the composite additive added to each ton of the molten steel is 0.51-4.9 kg.
Citation Information
Patent Citations
Composite core-spun yarn and large-line-energy welding steel preparing method
CN111500821A
Composite deoxidizer for oxide metallurgy and application
CN112442568A